The Influence of Movement Tempo During Resistance Training on Muscular Strength and Hypertrophy Responses: A Review - Wilk, Michal; Zajac, Adam; Tufano, James J (Sports medicine (Auckland, N.Z.), 2021)
Hypertrophy and strength are two common long-term goals of resistance training that are mediated by the manipulation of numerous variables. One training variable that is often neglected but is essential to consider for achieving strength and hypertrophy gains is the movement tempo of particular repetitions. Although research has extensively investigated the effects of different intensities, volumes, and rest intervals on muscle growth, many of the present hypertrophy guidelines do not account for different movement tempos, likely only applying to volitional movement tempos. Changing the movement tempo during the eccentric and concentric phases can influence acute exercise variables, which form the basis for chronic adaptive changes to resistance training. To further elaborate on the already unclear anecdotal evidence of different movement tempos on muscle hypertrophy and strength development, one must acknowledge that the related scientific research does not provide equivocal evidence. Furthermore, there has been no assessment of the impact of duration of particular movement phases (eccentric vs. concentric) on chronic adaptations, making it difficult to draw definitive conclusions in terms of resistance-training recommendations. Therefore, the purpose of this review is to explain how variations in movement tempo can affect chronic adaptive changes. This article provides an overview of the available scientific data describing the impact of movement tempo on hypertrophy and strength development with a thorough analysis of changes in duration of particular phases of movement. Additionally, the review provides movement tempo-specific recommendations as well real training solutions for strength and conditioning coaches and athletes, depending on their goals.
Keywords: svalová síla; Adaptation, Physiological; kosterní svaly; Muscle Strength; Hypertrophy; Muscle, Skeletal; lidé; hypertrofie; cvičení; odporový trénink; fyziologická adaptace; Exercise; Humans; Resistance Training